Analisis Perancangan Web Aplikasi Goffeeshop Dengan Metode Atomic Design Dan User Centered Design - Bendesa, Gde Agung Mandala; Raharja, Made Agung (Jurnal Nasional Teknologi Informasi dan Aplikasnya, 2022)
Design patterns in Software Engineering generally provide solutions to recurring problems that often occur in software design. The subjective difference in design style is one of the obstacles experienced by Front-End Developers in designing the user interface design of slicing software, making the process of designing user interface designs tends to take a long time. This is the background of the author to design a Design System with the Atomic Design method in designing Goffeeshop Web Applications. In this research will be carried out using the Atomic Design method in the design process and the overall process of this research will use the User Centered Design method in several stages that are adapted to the research. Based on the test results, the research can be seen that the System Design that is designed can increase the productivity of a Front-End Developer in the design so that the time used is reduced because by utilizing the concept of the Atomic Design method. In addition, the resulting system results are more uniform and consistent. Then tested with the concept of User Centered Design using a questionnaire before and after the research design in accordance with usability indicators. Testing with a questionnaire before design is carried out to find out the solution and researchers can decide to create this information system, then a questionnaire is carried out after the design is carried out to be able to measure the level of user satisfaction with the Goffeeshop Web Application that has been designed which in this study an average of 69.6% of respondents users say this system is very easy and suitable.